Production Optimization to Maximize Profit in Furniture Company PT. FurniCraft: Quantitative and Qualitative Approach - Khairunnisah, Noni Antika; Gunardi, Effendy; Kurnadi, Kurnadi; Setiawan, Iwan; Suparta, I Made (Business Management, 2025)
This study aims to optimize the amount of production to maximize profits at the furniture company PT. FurniCraft. The method used is a quantitative approach using Linear Programming (LP) and a qualitative approach using NVivo software to analyze the results of interviews with management. The LP model is used to determine the optimal product combination that maximizes profits based on resource limitations such as raw materials, working hours, and production capacity. Meanwhile, qualitative analysis reveals non-technical factors that affect the production process, such as workforce flexibility and production policies. The results of the analysis show that by implementing an optimization model, the company can increase potential profits by up to 18.5% from actual conditions. This finding is reinforced by the results of qualitative analysis which shows that production decisions are not entirely data-based, but rather more influenced by intuition and old habits. This study recommends the integration of analytical data in strategic decision making in the manufacturing sector.